Higher-rank quantum-classical correspondence - Hilgert, Joachim; Weich, Tobias; Wolf, L.

Justine Favarts Rox(el)ane: Eine Relektüre von Soliman second (1761) in Text, Bild, Musik jenseits des Orientalismusparadigmas - Münzmay, Andreas (Musikwissenschaft der Vielfalt. FS Rebecca Grotjahn zum 60. Geb.)
The conventional wisdom is that Favart's 'Soliman second' is, as Larry Wolff puts it, about an "explicitly French triumph over Ottoman despotism". This may be true to a certain extent - but it misses the point. As impressive as the depiction of the 'Oriental' may have been, it is not itself the core message of this comédie, but rather only one of the means to an end, which consists of once again accompanying and authenticating Justine Favart's novel, very modern approach to realistic character representation in the best possible way. This study demonstrates this by means of a combined analysis of the theatrical levels of text, image and music. Instead of orientalism in the sense of constructing images of the exotic 'other', the textual, pictorial and musical strategies employed in this play specifically conceived for Justine Favart apply to the production of theatrical 'authenticity' and 'natural' character representation in general. The fact that the stage persona thus brought to bear, i.e. the main character Roxelane, who responds to many models from Racine to Montesquieu, is a militantly enlightened and feminist one whose 'natural' persuasiveness and force no one can ultimately resist, so that Justine Favart's Roxelane triumphantly asserts herself all along the line and establishes nothing less than a new social, gender and state order, makes the matter all the more interesting.

Philip Ording: 99 Variations on a Proof. Princeton University Press 2019 - Hilgert, Joachim (Mathematische Semesterberichte)

Georg Glaeser (Hrsg.): 77-mal Mathematik für zwischendurch – Unterhaltsame Kuriositäten und unorthodoxe Anwendungen. Springer Spektrum 2020 - Hilgert, Joachim (Mathematische Semesterberichte)

Immaterielles Kulturerbe in der Coronakrise. Gesellschaftliche Bräuche, Rituale und Feste und die Folgen von Covid-19 am Beispiel des Schützenwesens - Leineweber, Jonas (Rheinisch-Westfälische Zeitschrift für Volkskunde)

Medien der Sorge, Techniken des Selbst. Praktiken des Über-sich-selbst-Schreibens bei Christoph Schlingensief und Elfriede Jelinek - Degeling, Jasmin

Mein Handy hat schon Covid-19!‘ Digitaler Faschismus unter Bedingung der Corona-Pandemie - Degeling, Jasmin (onlinejournal kultur&geschlecht)

Medien der Sorge. Einleitung in den Schwerpunkt - Degeling, Jasmin; Haffke, Maren (Zeitschrift für Medienwissenschaft. Jg. 13, Heft 24)

Students’ learning of computational thinking in schools with different curriculum approaches including individual student characteristics - Labusch, Amelie; Eickelmann, Birgit (Proceedings of the 5th APSCE International Computational Thinking and STEM in Education Conference 2021)

Schule digital – der Länderindikator 2021. Erste Ergebnisse und Analysen im Bundesländervergleich - Lorenz, R.; Yotyodying, S.; Eickelmann, Birgit; Endberg, M.

Gelingende digitale Schulentwicklung in der Post-Pandemiezeit - Eickelmann, Birgit (SchulVerwaltung Spezial)

Gelingende digitale Schulentwicklung in der Post-Pandemiezeit - Eickelmann, Birgit (SchulVerwaltung Spezial 2021)

Schule in der digitalen Welt - Buhl, Heike M.; Bonanati, Sabrina; Eickelmann, Birgit

Charakterisierung der Abscheideeffizienz eines kombinierten Abgasreinigungsverfahrens zur simultanen Minderung von partikulären und gasförmigen Emissionen - Wortmeier, Andreas; Beimdiek, Janis

Experimentelle Untersuchung zur Abscheidung von Stäuben aus häuslichen Holzfeuerungsanlagen mittels Schüttschichtfiltration - Buff, Jasmin; Beimdiek, Janis

Kunstunterricht planen, analysieren und reflektieren. Verknüpfung von Theorie und Praxis im Fach Kunst an der Universität Paderborn am Beispiel des Praxissemesters - Waffner, Annika; Schmidt, Rebekka (Fachdidaktische Entwicklung von Lehrkräften fördern)

Student engagement in digitalen Lehr-Lern-Szenarien. Zwei Fachdisziplinen berichten - Schmidt, Rebekka; Mindt, Ilka (Hochschule auf Abstand)

Vom Binge-Eating zu Yogakursen - Prikoszovits, Matthias (Sprache im Beruf)
Keywords: General Medicine

Data Literacy: Kompetenzrahmen für Hochschulen - Bush, Annika; de Gruisbourne, Birte; Matzner, Tobias; Schulz, Christian

Digital Masculinities. YouTube, Ästhetik und männliche Körper - Hoffarth, Britta; Richter, Susanne; Wehren, Sylvia (Buzzword Digitalisierung: Kritische Perspektiven auf Digitalisierung im Kontext von Geschlecht und Vielfalt)

Hallo Schönheiten! Performances und Aushandlungen der Geschlechterordnung in der YouTube-Beauty-Community - Richter, Susanne
Keywords: {<}3

Am Herzen liegen und horchen. Eine Antwort auf das Tötungsverbot durch eine ethische Rechtfertigung eines Menschenrechts auf Leben - Kaup, Michael
Wie rechtfertigen wir die ethische Legitimität eines Tötungsverbots und wo liegen die Grenzen des Verbots? Die vorliegende Arbeit versucht eine ethische Grundlage für ein Tötungsverbot über ein Menschenrecht auf Leben zu erarbeiten: Wie lässt sich ethisch ein Menschenrecht auf Leben rechtfertigen? Die Antwort darauf mündet in der Erkenntnis, dass Menschen ein Menschenrecht auf Leben als einen Bestandteil ihrer Lebensführung und als eine Antwort auf die Frage, wie wir leben wollen, begreifen, um zu einer gesicherten ethischen Grundlage zu gelangen.
Keywords: Tötungsverbot; Recht auf Leben; Menschenrecht auf Leben

Review of: Wie die Welt in den Computer kam: Zur Entstehung digitaler Wirklichkeit [How the world came to be in the computer: On the creation of digital reality] by David Gugerli - Schmitt, Martin (Technology and Culture)

Die Digitalisierung der Kreditwirtschaft. Computereinsatz in den Sparkassen der Bundesrepublik und der DDR 1957-1991 - Schmitt, Martin

Weltweite Verfügbarkeit und digitale Langzeitarchivierung - Ried, Dennis (Mitteilungen der IMRG)

Musikalische Schrift und Digitalität. Ein Werkstattbericht - Freund, Julia; Muennich, Stefan; Ried, Dennis; Ziegler, Michelle

Lieder II

Der Liebe will ich singen. Hermann Reutters Begegnung mit dem Mittelalter - Ried, Dennis (Ritter, Tod und Teufel. Hermann Reutter und das Lied)

Werke für gemischten Chor a cappella II

A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

Model based random packing optimisation for absorption processes using the hydrodynamic analogy concept - Salten, Alexander Heinrich Johannes; Kenig, Eugeny (Chemical Engineering Science)

Investigation of the pressure-throughput behavior of different faceted mixer geometries on an analytical and simulative basis - Frank, Maximilian; Hollenhorst, Viola; Schöppner, Volker (36th International Conference of the Polymer Processing - PPS 2021)

Development of a Dynamic Modeling Approach to Simulate a Segmented Distillation Column for Flexible Operation - Bruns, Bastian; Fasel, Henrik; Grünewald, Marcus; Riese, Julia (ChemEngineering)
The need for flexible process equipment has increased over the past decade in the chemical industry. However, process equipment such as distillation columns have limitations that significantly restrict flexible operation. We investigate a segmented tray column designed to allow flexible operation. The design consists of radial trays connected at the downcomer of each tray. Each segment can be operated separately, but depending on the capacity of the feed stream, additional segments can be activated or deactivated. The connection between the trays aims to transfer liquid from one stationary segment to the adjacent inactive segment, thereby reducing the time required for the start-up process. In a case study on the separation of methanol and water, we perform dynamic simulations to assess the reduction in the start-up time of inactive segments. The results confirm the advantages over standard tray designs. The segmented distillation column is a step towards improving the flexibility of separation operations.
Keywords: General Energy; General Engineering; General Chemical Engineering

Concept of a Flexible Wetted‐Wall Column for the Distillation of Specialty Chemicals - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Chemical Engineering & Technology)
Abstract The trend of increasing product diversity and decreasing production amounts led to the requirement of higher flexibility of production processes of specialty chemicals. Conventional distillation columns, mostly equipped with structured packings, lack the flexibility to handle product changeovers and throughput. Thus, a newly designed distillation column for specialty chemicals is presented. A numerical model was implemented to analyze the potential of the wetted‐wall column. The simulation of the distillation of a binary methanol/water mixture demonstrated that the wetted‐wall column can generate the desired concentration and temperature profiles. Furthermore, analyses of the pressure drop and separation efficiency with the test system chlorobenzene/ethylbenzene were conducted.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Characterization of Liquid-Phase Distribution in 3D Printed Structured Packings with an Enclosed Column Wall - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Flexibility analysis for demand-side management in large-scale chemical processes: An ethylene oxide production case study - Bruns, Bastian; Di Pretoro, Alessandro; Grünewald, Marcus; Riese, Julia (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Indirect Demand Response Potential of Large-Scale Chemical Processes - Bruns, Bastian; Di Pretoro, Alessandro; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Dynamic Design Optimization for Flexible Process Equipment - Bruns, Bastian; Herrmann, Felix; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Efficient Production of Specialized Polymers with Highly Flexible Small‐Scale Plants - Bruns, Bastian; Becker, Tristan; Riese, Julia; Lier, Stefan; Werners, Brigitte (Chemical Engineering & Technology)
Abstract Shortened product life cycles and increased demand for specialized products lead to more challenges in efficiently satisfying customer needs. Customer demands are increasingly uncertain in terms of type, location, and volume. As a result, more flexible chemical production plants are required. Modular small‐scale plants can be installed in transportation containers and, therefore, offer the flexibility of easy relocation, enabling production close to the customer or supplier. In a mathematical optimization model, the economic benefit of small‐scale plants in the specialty chemicals market of polymer production is analyzed. Different scenarios created from the real data of a chemical company show that the use of small‐scale plants may lead to a significant reduction in total costs that is mainly due to the transportation costs of raw materials and products.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Experimentelle Untersuchungen zum Tropfenmitriss im Feedeinleitbereich von Destillationskolonnen - Fasel, Henrik; Darvishsefat, Novin; Riese, Julia; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Im Rahmen dieses Beitrags werden experimentelle Untersuchungen zur Tropfenabscheidung im Einleitbereich eines Stoffaustauschapparates für zweiphasige Strömungen vorgestellt. Dafür wurde in einem Versuchsstand im Pilotmaßstab der qualitative Tropfenmitriss für unterschiedliche Tropfenabscheider eines Stoffaustauschapparates vermessen. Die daraus resultierenden Ergebnisse werden in diesem Beitrag hinsichtlich ihrer Aussagekraft zur Vermeidung von Tropfenmitriss diskutiert und bewertet. Darüber hinaus wird ein kurzer Ausblick über simulative Arbeiten zur Bestimmung des Tropfenmitriss gegeben.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Heat transfer enhancement within internally channeled tubes - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y.

Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Sheet Metal 2021)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Tribology; Sheet Metal; Simulation

"Lobe den Herren, den mächtigen König der Ehren" - Ein Lied mit Lebensbezug - Breckner, Anne (Musik als Lebensmittel: Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Conference Report: Dynamics of Tradition: Islamic Theology and Law in Relation (September 17-19, 2021, Paderborn) - Nassery, Idris; Tatari, Muna; Mustafa, Abdul Rahman

Our Energy Grids as Enabler for More Sustainability. Talk - Schlüter, Alexander

Wir müssen handeln: Jetzt! - Schlüter, Alexander; Bernabé-Moreno, Juan (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Wer grüne Energie will, muss auch koppeln und speichern - Meschede, Henning; Khripko, Diana; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities and Smart Rural Areas)

Insights into the Future Energy System in Smart Cities and Rural Areas. Talk - Schlüter, Alexander

Effect of Solidification Rates at Sand Casting on the Mechanical Joinability of a Cast Aluminium Alloy - Neuser, Moritz; Grydin, Olexandr; Andreiev, Anatolii; Schaper, Mirko (Metals)
Implementing the concept of mixed construction in modern automotive engineering requires the joining of sheet metal or extruded profiles with cast components made from different materials. As weight reduction is desired, these cast components are usually made from high-strength aluminium alloys of the Al-Si (Mn, Mg) system, which have limited weldability. The mechanical joinability of the cast components depends on their ductility, which is influenced by the microstructure. High-strength cast aluminium alloys have relatively low ductility, which leads to cracking of the joints. This limits the range of applications for cast aluminium alloys. In this study, an aluminium alloy of the Al-Si system AlSi9 is used to investigate relationships between solidification conditions during the sand casting process, microstructure, mechanical properties, and joinability. The demonstrator is a stepped plate with a minimum thickness of 2.0 mm and a maximum thickness of 4.0 mm, whereas the thickness difference between neighbour steps amounts to 0.5 mm. During casting trials, the solidification rates for different plate steps were measured. The microscopic investigations reveal a correlation between solidification rates and microstructure parameters such as secondary dendrite arm spacing. Furthermore, mechanical properties and the mechanical joinability are investigated.

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, M; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, T (IOP Conference Series: Materials Science and Engineering)